The microRNA-29a Modulates Serotonin 5-HT7 Receptor Expression and Its Effects on Hippocampal Neuronal Morphology - Floriana Volpicelli; L. Speranza; S. Pulcrano; R. De Gregorio; M. Crispino; C. De Sanctis; M. Leopoldo; E. Lacivita; U. di Porzio; G. C. Bellenchi; C. Perrone-Capano (Molecular Neurobiology, 2019)

Affiliations between bacteria and marine fish leeches (Piscicolidae), with emphasis on a deep‐sea species from Monterey Canyon, CA - S. K. Goffredi; N. M. Morella; M. E. Pulcrano (Environmental Microbiology, 2012)
Summary Leeches within the Piscicolidae are of great numerical and taxonomic importance, yet little is known about bacteria that associate with this diverse group of blood‐feeding marine parasites of fish and elasmobranchs. We focused primarily on the bacteria from a deep‐sea leech species of unknown identity, collected at ∼ 600 m depth in Monterey Canyon, CA, along with two shallow‐living leech genera, Austrobdella and Branchellion , from Los Angeles Harbor, CA. Molecular analysis of all five leech species revealed a dominance of gammaproteobacteria, which were distinct from each other and from previously reported freshwater leech symbionts. Bacteria related to members of the genus Psychromonas (99% similarity in 16S rRNA) were dominant in the deep‐sea leech species (80–94% of recovered ribotypes) collected over 19 months from two different locations. Psychromonas was not detected in cocoons or 2–16 week‐old juveniles, suggesting that acquisition is via the environment at a later stage. Transmission electron microscopy did, however, reveal abundant bacteria‐like cells near areas of thinning of the juvenile epithelial surface, as well as Psychromonas sparsely distributed internally. Electron and fluorescence in situ microscopy of adults also showed Psychromonas ‐like bacteria concentrated within the crop. Despite the apparent non‐transient nature of the association between Psychromonas and the deep‐sea leech, their functional role, if any, is not known. The prevalence, however, of an abundant bacterial genus in one piscicolid leech species, as well as the presence of a dominant bacterial species in singular observations of four additional marine species, suggests that members of the Piscicolidae, possibly basal within the class Hirudinea, form specific alliances with microbes.